Evaluating the Depth–Age Hypothesis for the Evolution of the Lunar Regolith - Gwendolyn D. Bart (The Planetary Science Journal)
Lunar regolith is the fractured rock layer covering most of the lunar surface. This rock is fractured into regolith primarily by repeated meteorite impacts over eons. The depth of the regolith is determined by the maximum depth reworked by impactors. Older surfaces are expected to have thicker regoliths because they have been exposed to longer periods of bombardment than younger surfaces—a concept I refer to as the Depth–Age Hypothesis. To test the hypothesis, I compare published, measured regolith depths on mare basalts with published, measured surface ages of those mare. If the Depth–Age Hypothesis is correct, older mare surfaces should have thicker regoliths than younger surfaces. Contrary to the hypothesis, published data show that both younger and older lunar surfaces have median regolith depths ranging from about 3 to 9 m. Possible reasons for this finding include variations among measurement methods, reporting regolith depths with too great precision, and the inherent variability of the lunar regolith.